Omega-3 fatty acid ameliorates bisphenol F-induced testicular toxicity by modulating Nrf2/NFkB pathway and apoptotic signaling - Odetayo, Adeyemi Fatai; Adeyemi, Wale Johnson; Olayaki, Luqman Aribidesi (Frontiers in Endocrinology, 2023)
Bisphenol F (BPF) has been shown to disrupt testicular functions via perturbation of testicular redox balance, while omega-3 fatty acid (O3FA) has been established to exert antioxidant and anti-inflammatory activities. Therefore, this study focused on the role and associated molecular mechanism of O3FA in BPF-induced testicular dysfunction in male Wistar rats. Twenty-four (24) rats were randomly grouped after two weeks of acclimatization into four (4) groups (n=6/group); the vehicle-treated control group, BPF treated group received 30 mg/kg of BPF, and the intervention groups received 30 mg/kg BPF + 100 mg/kg O3FA (BPF+O3FA-L) and 30 mg/kg BPF + 300 mg/kg of O3FA (BPF+O3FA-H). All treatment lasted for 28 days. Low and high doses of O3FA ameliorated BPF-impaired sperm quality, and induced hormonal imbalance, accompanied by a distortion in testicular histology and elevated testicular injury markers. Furthermore, coadministration of BPF with both doses of O3FA blunted BPF-induced redox imbalance, inflammatory response, and apoptosis. In conclusion, our present findings show that O3FA improves testicular functions in BPF-treated rats by improving sperm quality and reproductive hormones via the maintenance of testicular redox balance.